MINERALOGY, GEOCHEMISTRY AND PETROGENESIS OF KURILE ISLAND-ARC BASALTS - Bailey J.C.; Frolova T.I.; Burikova I.A. (My University, 1989)
Whole-rock (major- and trace-element) and mineral chemical data are presented for basaltic rocks from the main evolutionary stages of the Kurile island arc, NW Pacific. An outer, inactive arc contains a Cretaceous-Lower Tertiary sequence of tholeiitic, calcalkaline and shoshonitic basalts. The main arc (Miocene-Quaternary) is dominated by weakly tholeiitic, with lesser, alkalic basalts. The mineralogy of Kuriles basalts is characterised by An-rich plagioclases, a continuous transition from chromites to titanomagnetites, pyroxenes with low Fe3+ contents and without strong Fe-enrichment, abundance of groundmass pigeonites and the absence of amphiboles. There is an increase in K2O contents both along-arc (northwards) and towards the reararc side. The basalts show an exceptionally wide but continuous range of K2O contents (0.1–4.7%) which correlate with other LIL element contents. Tholeiitic basalts with low LIL element contents, La/Yb and Th/U, but high K/ Rb, P2O5/La and Zr/Nb were derived from depleted, lherzolitic mantle which had suffered fluid metasomatism by K, Rb, Cs, Sr, Ba, Pb and H2O only. Alkali basalts are also thought to be derived from depleted mantle but melt metasomatism involved addition of all LIL elements to a garnet lherzolite mantle. The Kuriles basalts and their mantle sources range continuously between these two end-member compositions. The metasomatic fluids/melts were probably released by early dehydration and later melting within subducted oceanic lithosphere though the process is not adequately constrained.
Keywords: Quaternary; Cretaceous; Miocene; Mesozoic::Cretaceous; Cenozoic::Neogene::Miocene; Cenozoic::Quaternary; Мезозой::Меловая; Кайнозой::Неоген::Миоцен; Кайнозой::Четвертичная